A prediction of the CRNDE role by modulating NF-κB pathway in inflammatory bowel disease (IBD) - Nesa Kazemifard; Maryam Farmani; Shaghayegh Baradaran Ghavami; Mohammad Kazemi; Shabnam Shahrokh; Hamid Asadzadeh Aghdaei; Mohammadreza Zali (Biochemistry and Biophysics Reports, 2024)
Long non-coding RNAs (lncRNAs) regulate multiple pathways and cellular mechanisms. Recent research has emphasized their involvement in the pathogenesis of complex diseases, such as Inflammatory Bowel Disease (IBD) which is characterized by chronic inflammation of the intestines. The two most common types of IBD are ulcerative colitis and Crohn's disease. CRNDE lncRNA was initially detected in colorectal cancer (CRC) and found to be involved in the tumorigenesis pathways. Further studies revealed the role of CRNDE in activating inflammation and promoting the release of inflammatory cytokines. This study utilizes the RNA-seq data analysis and bioinformatics tools to clarify the role of CRNDE in the IBD pathogenesis and confirms its expression in inflamed HT-29 and Caco-2 cell lines and also colonic and blood samples of UC patients and controls ex vivo. Based on our results, CRNDE was significantly upregulated in IBD samples compared to controls in RNA-seq data analysis and Real-time PCR of inflamed HT-29 cell line and colonic biopsies from UC patients. Additionally, predicted that its expression is positively correlated with the pro-inflammatory cytokines production. CRNDE interactions was investigated with several inflammation-related miRNAs and regulatory proteins computationally. Thus, CRNDE upregulation in the colon of IBD patients could be involved in IBD pathogenesis by promoting inflammatory pathways and targeting anti-inflammatory miRNAs.